COEVOLUTION IN «A PREDATOR–PREY» SYSTEM: AN ECOGENETIC MODEL - Yu. S. (Вавиловский журнал генетики и селекции, 2015)
In most natural populations, intraspecies competition for natural resources is supplemented by a predator impact. We suppose that the mode and intensity of the interaction between a prey and its predator affects the course of competitive or sympatric speciation among the prey and processes of co-evolution or cospeciation. Mathematical methods allow development of models precisely describing all sides of intra and interspecies interactions. In this paper, we use mathematical modeling to investigate the effect of the intensity of interspecies interactions on competitive or sympatric speciation inside a prey population. The iIntensity of the interaction is the average number of prey which predators eat in a unit of time: the higher is the number of prey eaten by predators, the greater is the intensity of the interaction. In mathematical models, the intensity of such interaction is determined by many parameters. Changes in these parameters will affect the intensity of the interaction. It was found that sufficiently high intensity of interaction slows down competitive speciation among the prey. The preys in this case, seeking to avoid the impact of predators by altering their adaptive traits. Another important result was that the speciation of predators follows prey speciation when the probability of mutational changes in adaptive traits of predators exceeds that in the prey.